Peran public relation dalam meningkatkan citra perbankan syariah di Indonesia - Faricha, Risalatul (Maliki Interdisciplinary Journal, 2025)
The development of Islamic banking in Indonesia shows a positive trend, as public awareness of an economic system based on Islamic values ​​increases. However, despite this growth, challenges remain in building a positive image of Islamic banking in the public eye. This study aims to analyze the role of Public Relations (PR) in improving the image and public trust in Islamic banking. The research method used is a desk study, reviewing various relevant literature, scientific journals, and secondary data. Therefore, PR plays a crucial role in strengthening the image and sustainability of Islamic banking in Indonesia. Support from the government, regulators, and financial institutions is needed to expand Islamic financial literacy nationally so that Sharia values ​​and principles can be more widely accepted.